Interdisciplinary legal studies the next generation - Sarat, Austin (Emerald, 2010)
This volume of Studies in Law, Politics, and Society brings together research by graduate students from universities in the United States and the United Kingdom. The work of these students was singled out by their teachers and advisors as showing unusual promise and marking out directions for the next generationA" of interdisciplinary legal scholars. The research collected here is often comparative. It is theoretically informed and rigorous in its methods. Taken together it shows breadth and excellence, and it signals the continuing vibrancy of interdisciplinary legal studies.
Keywords: Sociological jurisprudence.; Law and the social sciences.; Law & society.; Courts & procedure.; Law -- General.; Law -- Trial Practice.; elektronické knihy; electronic books